2015
DOI: 10.1002/14651858.cd011583.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Nut consumption for the primary prevention of cardiovascular disease

Abstract: Currently there is a lack of evidence for the effects of nut consumption on CVD clinical events in primary prevention and very limited evidence for the effects on CVD risk factors. No conclusions can be drawn and further high quality longer term and adequately powered trials are needed to answer the review question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 122 publications
0
10
0
Order By: Relevance
“…In a meta-analysis and dose–response of sixty-one controlled intervention trials, which ranged in duration from 3 to 26 weeks, the consumption of nuts was associated with significant reductions in TC, LDL-C, apoB and TAG, with greater effects observed with a nut intake of 60 g/d and in individuals with T2DM ( 29 ) . In contrast, in a Cochrane review, Martin et al ( 30 ) reported that the intake of nuts had no effects on LDL-C or HDL-C (for TC and TAG, substantial heterogeneity precluded the pooling of results). The Cochrane assessment was based only on three publications (and four strata): Tey et al ( 31 ) (who provided 42 g of hazelnuts to generally healthy male and female adults for 12 weeks); Abazfarad et al ( 9 ) (who provided 50 g of almonds to overweight and obese premenopausal women for 3 months); and Tey et al ( 32 ) (who provided 30 or 60 g of hazelnuts to overweight and obese male and female adults for 12 weeks).…”
Section: Discussionmentioning
confidence: 96%
“…In a meta-analysis and dose–response of sixty-one controlled intervention trials, which ranged in duration from 3 to 26 weeks, the consumption of nuts was associated with significant reductions in TC, LDL-C, apoB and TAG, with greater effects observed with a nut intake of 60 g/d and in individuals with T2DM ( 29 ) . In contrast, in a Cochrane review, Martin et al ( 30 ) reported that the intake of nuts had no effects on LDL-C or HDL-C (for TC and TAG, substantial heterogeneity precluded the pooling of results). The Cochrane assessment was based only on three publications (and four strata): Tey et al ( 31 ) (who provided 42 g of hazelnuts to generally healthy male and female adults for 12 weeks); Abazfarad et al ( 9 ) (who provided 50 g of almonds to overweight and obese premenopausal women for 3 months); and Tey et al ( 32 ) (who provided 30 or 60 g of hazelnuts to overweight and obese male and female adults for 12 weeks).…”
Section: Discussionmentioning
confidence: 96%
“…-supplements: vitamin C 12 , antioxidant 13 , vitamin D 14 , selenium 15 , vitamin Co-enzyme Q10 16 , vitamin K 17 , and vitamin, mineral and multivitamin supplements 18 . Fortmann's review 22 included different interventions based on single and paired combination of supplementation with vitamins and minerals supplementation, including vitamin C and selenium. The two reviews on vitamin C 12,18 shared elements such as type of population included and intervention, but they differed in both the outcome measures included and some inclusion criteria (minimum follow-up time for required randomized controlled trials (RCT) (three months) 12 , trials with good or fair quality, studies carried out in countries whose Human Development Index was considered very high 18 )…”
Section: Primary Preventionmentioning
confidence: 99%
“…The overall number of participants included in these systematic reviews ranged between 60 participants 20 and 215,900 participants for antioxidant supplementation 13 . Only four reviews included less than 500 participants 16,17,22,32 . The number of trials per review ranged between one 17 and 55 19 .…”
Section: Primary Preventionmentioning
confidence: 99%
See 2 more Smart Citations